2017
DOI: 10.11138/orl/2017.10.4.360
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Post-Space Depth Reading With an Intraoral Scanner (Ios) Compared to a Traditional Silicon Impression

Abstract: SUMMARYObjectives. The aim of the study was to assess the depth and quality of the post-space reading, using an IOS without scanpost, compared to a traditional silicon technique. Methods. Six extracted bicuspids were decoronated and endodontically treated. After having prepared the space for the posts, a structure in pink acrylic resin was created with two resin elements. At the center of the structure one sample was put at a time. Digital and traditional impressions were taken for each sample. Digital impress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
(31 reference statements)
0
14
1
Order By: Relevance
“…IOS was suggested to be a reliable alternative in the clinical practice to conventional impression methods in the manufacture of implant-supported crowns and short-span fixed dental prostheses [ 22 ]. Moreover, digital implant impressions could offer advantages over conventional impressions, such as reduced risks of distortion during the impression and laboratory phases, improved patient comfort and acceptance, and improved time efficiency [ 23 , 24 ]. However, digital workflow is still subject to errors, which could derive from the digital impression and CAD/CAM software, as well as production (subtractive or additive) manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…IOS was suggested to be a reliable alternative in the clinical practice to conventional impression methods in the manufacture of implant-supported crowns and short-span fixed dental prostheses [ 22 ]. Moreover, digital implant impressions could offer advantages over conventional impressions, such as reduced risks of distortion during the impression and laboratory phases, improved patient comfort and acceptance, and improved time efficiency [ 23 , 24 ]. However, digital workflow is still subject to errors, which could derive from the digital impression and CAD/CAM software, as well as production (subtractive or additive) manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study by Pinto et al [18] compared digital and conventional impression techniques for CAD/CAM-P+C with regard to impression depth. The investigated area was compared to the apical measurement area in the present study.…”
Section: Digital Impression Taking With Ios (Part A)mentioning
confidence: 99%
“…There are two possible sources of error during the manufacturing of CAD/CAM-P+C: inaccuracies within intraoral scanning of prepared root canals [18], and manufacturingrelated inaccuracies due to CAD/CAM milling [17,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 5 ] Some studies have shown that intraoral scanners are less accurate when capturing details of full arch reconstructions or postpreparations. [ 6 7 ] Scanners also are less suited for capturing subgingival details when preparations of teeth are cervical to the gingival margin. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%